PELATIHAN PUBLIC SPEAKING BAGI ANAK-ANAK KOMUNITAS MAT PECI CILIWUNG UNTUK MENINGKATKAN PARTISIPASI PUBLIK DALAM ISU LINGKUNGAN - M. Fikri Akbar; Sandy Allifiansyah; Mutmainah, Mia; Muhammad Dika Octaviano; Gina Rahmani; Zacky Sazari Putra (JURNAL ABDIMAS DOSMA (JAD), 2025)
This service focuses on improving the public speaking skills of the children of the Mat Peci Ciliwung Community to encourage public participation in environmental issues. The goal is to equip children with effective communication skills and confidence in conveying ideas. The implementation methods include socialization, interactive training, speaking simulations, and ongoing mentoring and evaluation. Participatory and educational approaches are used to adjust the material to the needs of the participants. The results of the service show a significant increase in children's confidence in public speaking, as demonstrated by their enthusiasm when practicing speaking and involvement in discussions. This program also provides a strong foundation for the desire to train and strengthen the role of children in voicing environmental issues in their communities.